Rethinking fiscal federalism in the Federation of Bosnia and Herzegovina - Kršo, Mirza (Central European Public Administration Review, 2026)
Purpose: This paper develops and operationalises a transparent, rule-based model of horizontal equalisation for the Federation of Bosnia and Herzegovina (FBiH) and assesses its multi-year effects on disparities in fiscal capacity. It addresses a setting in which institutional asymmetry and weak central coordination have produced persistent vertical and horizontal fiscal imbalances. Design/methodology/approach: The paper combines comparative institutional analysis with a data-driven assessment of horizontal disparities. Using cantonal-level data for FBiH for the period 2018–2024, the results are interpreted within an empirical scope that excludes municipal arrangements because comparable data are unavailable and because vertical-balance issues remain politically sensitive; these issues are therefore identified as priorities for future research. The article specifies a two-pillar allocation rule: (I) a derivation share and (II) a capacity-based equalisation fund with an 80 per cent post-equalisation floor. “Before/ after” allocations are compared using subnational data for 2018–2024 at the cantonal level. Because consumption is unobserved, income is used as a residence-based proxy for VAT. Effects are tracked through the mean share of FBiH, the Gini coefficient, and the coefficient of variation, while eligibility for Pillar II is dynamic: cantons below 100 per cent before equalisation qualify each year. Findings: The simulation results indicate that the proposed model achieves significant horizontal equalisation without weakening fiscal incentives for better-performing cantons. System-wide, mean fiscal capacity rises from 88 per cent to 99 per cent of the FBiH average, while both the Gini coefficient and the coefficient of variation fall by roughly one half. Among dynamically eligible cantons, the effects are even more pronounced: the mean rises by 19 percentage points and dispersion falls by 70 per cent. High-capacity cantons remain above 100 per cent after equalisation, indicating that the model avoids over-equalisation. The results remain robust through the COVID-19 and inflation years, supporting a four-year recalibration principle. Academic contribution to the field: The paper specifies and audits a transparent two-pillar model for FBiH, centred on the per-capita fiscalcapacity gap and an 80 per cent adequacy floor calibrated to secure a comparable minimum while keeping high-capacity cantons above 100 per cent after equalisation. By connecting fiscal design with questions of institutional fairness, territorial cohesion, and rule-based governance, the article contributes to wider debates on fiscal federalism in politically fragmented systems. Because destination-based VAT, asymmetric territorial status, and reliance on proxy measures of consumption are common in federations and regional unions, the two-pillar design developed for FBiH is presented as a transferable template for converting politically negotiated tax-sharing coefficients into transparent, rule-based allocations. Research limitations/implications: The analysis uses income as a residence- based proxy for the VAT base because canton-level consumption data are unavailable. It targets horizontal fiscal capacity only; expenditure needs, cost disabilities, and municipal disparities are not modelled. The parameters, namely the 80 per cent floor and 25 per cent pool, are calibrated rather than estimated, and the simulations are mechanical rather than behavioural. Future work should triangulate proxies, such as retail turnover and VAT administrative aggregates, add cost-need modules, test parameter sensitivity, and apply panel and behavioural methods to inform the four-year recalibration. Practical implications: The framework replaces coefficient-based bargaining with rule-based, auditable allocations that preserve incentives, reduce inter-cantonal tensions, and improve predictability. It also informs two governance steps: centralising external debt service at the federallevel with transparent revenue-share compensation, and phasing in capped, performance-sensitive grants indexed to the indirect-tax pool. A four-year review anchors outcomes to the adequacy floor as fiscal and institutional conditions evolve. Social implications: By promoting convergence towards a minimum standard of fiscal capacity, the model supports equity, cohesion, and legitimacy in public finance. Transparent, rule-bound allocation can strengthen trust in institutions, improve service provision in underfunded areas, and contribute to more balanced territorial development. Originality/significance/value: The paper presents an implementable equalisation rule tailored to a highly decentralised federation and tested on 2018–2024 subnational data that include the COVID-19 and inflation shocks. It shows how an explicit floor, calibrated pool, and dynamic eligibility can compress disparities without over-equalising high-capacity jurisdictions, offering a replicable template for reform-minded federations facing similar institutional and fiscal challenges.
Keywords: avna uprava; fiscal equalization; fiscal federalism; fiscal gap; fiskalna izravnava; fiskalna vrzel; fiskalni federalizem; horizontal imbalances; horizontalna neravnovesja; public administration; transitional economies; tranzicijska gospodarstva